2018
DOI: 10.1002/ejoc.201801003
|View full text |Cite
|
Sign up to set email alerts
|

The Conformation of the Mannopyranosyl Phosphate Repeating Unit of the Capsular Polysaccharide of Neisseria meningitidis Serogroup A and Its Carba‐Mimetic

Abstract: Neisseria meningitidis serogroup A (MenA) is an aerobic diplococcal Gram‐negative bacterium responsible for epidemic meningitis disease. Its capsular polysaccharide (CPS) has been identified as the primary virulence factor of MenA. This polysaccharide suffers from chemical lability in water. Thus, the design and synthesis of novel and hydrolytically stable structural analogues of MenA CPS may provide additional tools for the development of therapies against this disease. In this context, the structural feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…However, only carbaMenA DP8 competed for binding of an anti-MenA functional mAb, indicating that 8 repeating units are required to provide an effective synthetic antigen. While in silico analysis of carbaMenA related monomers has shown similar conformations with the natural sugar 54 , studies with oligomers up to the dodecamer have indicated that these longer structures may adopt a different overall conformation than their natural counterparts 55 . The results presented here show that the carbaMenA can adequately mimic the natural polysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…However, only carbaMenA DP8 competed for binding of an anti-MenA functional mAb, indicating that 8 repeating units are required to provide an effective synthetic antigen. While in silico analysis of carbaMenA related monomers has shown similar conformations with the natural sugar 54 , studies with oligomers up to the dodecamer have indicated that these longer structures may adopt a different overall conformation than their natural counterparts 55 . The results presented here show that the carbaMenA can adequately mimic the natural polysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…The trimer 26 was able to induce specific anti‐MenA IgG antibodies with detectable bactericidal activity in vitro, suggesting that carba‐analogues can be used for the development of synthetic vaccines . Interestingly, the conformational behavior of these analogues was also investigated, showing that the carbasugar mimics preserved the 4 C 1 geometry of the corresponding natural fragments.…”
Section: Endocyclic Oxygen Replacementmentioning
confidence: 99%
“…Ta ble 3g athers the results for the CPS Ia pentasaccharide 1.T he comparison reflectsagood agreement between the NMR-a nd the MD-derived distances for the glycosidicl inkages GlcNAcb1-3Gal and Glcb1-4Gal (defined by the interprotond istances H1GlcNAc-H3Gal and H1Glc-H4Gal, respectively). The F/Y population analysisf rom the MD simulation showedasingle population for F fulfillingt he exoanomeric effect (exo-syn-F), [29,30] and two populations around y for both linkages (Supporting Information, Figure S1).…”
Section: Conformational Analysismentioning
confidence: 99%